Fungal contamination in green coffee beans samples: a public health concern - Viegas, Carla (2017)
Studies on the microbiology of coffee cherries and beans have shown that the predominant toxigenic fungal genera (Aspergillus and Penicillium) are natural coffee contaminants. The aim of this study was to investigate the distribution of fungi in Coffea arabica L. (Arabica coffee) and Coffea canephora L. var. robusta (Robusta coffee) green coffee samples obtained from different sources at the pre-roasting stage. Twenty-eight green coffee samples from different countries of origin (Brazil, Timor, Honduras, Angola, Vietnam, Costa Rica, Colombia, Guatemala, Nicaragua, India, and Uganda) were evaluated. The fungal load in the contaminated samples ranged from 0 to 12330 colony forming units (CFU)/g, of which approximately 67% presented contamination levels below 1500 CFU/g, while 11% exhibited intermediate contamination levels between 1500 and 3000 CFU/g. Contamination levels higher than 3000 CFU/g were found in 22% of contaminated coffee samples. Fifteen different fungi were isolated by culture-based methods and Aspergillus species belonging to different sections (complexes). The predominant Aspergillus section detected was Nigri (39%), followed by Aspergillus section Circumdati (29%). Molecular analysis detected the presence of Aspergillus sections Fumigati and Circumdati. The% coffee samples where Aspergillus species were identified by culture-based methods were 96%. Data demonstrated that green coffee beans samples were contaminated with toxigenic fungal species. Since mycotoxins may be resistant to the roasting process, this suggests possible exposure to mycotoxins through consumption of coffee. Further studies need to be conducted to provide information on critical points of coffee processing, such that fungal contamination may be reduced or eliminated and thus exposure to fungi and mycotoxins through coffee handling and consumption be prevented.